Pengaruh Pembebanan Transformator Distribusi 3 Fasa 250 kVA Type Core Terhadap Distribusi Termal Menggunakan Perangkat Lunak Ansys Maxwell - Muljono, Agung Budi; Dharma, Ida Bagus Aditya Laksamana; Citarsa, Ida Bagus Fery (Jurusan Teknik Elektro Fakultas Teknik Universitas Mataram, 2025)
Distribution transformers have an important role in the distribution of electrical power. In order for the transformer to operate properly, installation and maintenance must be in accordance with established standards. One of the things that affects the condition of the transformer is the heat that arises as a result of loading. This study performs calculations manually to determine the dimensions of the transformer, make a model of the transformer core and coil in 3D visual form then analyze the output of voltage, current, and loss waves and analyze the distribution of the transformer's thermal field using Ansys Maxwell software with the Finite Element Method (FEM) method. This research refers to a catalog that contains specification data from transformers. For the simulation results obtained, the conditions of thermal distribution in the transformer core when the transformer was not given a load obtained an average temperature of 29.74 °C. Whereas when given the load, the temperature increases to 71°C. The thermal distribution spreads evenly throughout the transformer core. For the value of loss–the loss generated in a no-load transformer is 756.617 W and, in a transformer, when given a load of 1.014 W.